2011
DOI: 10.1111/j.1447-0756.2010.01501.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in local treatment of cervical heterotopic pregnancy with successful perinatal outcome: Case report

Abstract: This case report describes a case of heterotopic cervical ectopic pregnancy in a nulliparous woman that was successfully treated with single-dose local, intra-amniotic methotrexate injection in the gestational sac. Pregnancy was achieved spontaneously. The patient had previously undergone hysteroscopic myomectomy. By using local, single-dose treatment we avoided the continued effects of the drug on the intrauterine pregnancy and the possible adverse effect of systemically applied methotrexate. The treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 17 publications
(20 reference statements)
0
32
0
Order By: Relevance
“…HP, which has an increasing incidence due to widespread use of assisted reproduction techniques in infertile patients, is an important obstetric problem that can cause maternal and foetal mortality if not diagnosed at an early stage [5,6]. It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HP, which has an increasing incidence due to widespread use of assisted reproduction techniques in infertile patients, is an important obstetric problem that can cause maternal and foetal mortality if not diagnosed at an early stage [5,6]. It has been suggested that a delay in diagnosis can cause maternal mortality of 1% and foetal mortality of 45-65% [2].…”
Section: Discussionmentioning
confidence: 99%
“…Conservative surgery and medical therapy should be employed in cases without haemodynamic instability and rupture, as well in those who want to have children. Laparoscopic salpingostomy is frequently used in conservative surgery, and injection of potassium chloride and methotrexate into the ectopic gestational sac is used in medical therapy [4,5,6,8]. When a review of the literature, it is obvious that there is no unique attitude in medical treatment of HP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 3 cases of successful preservation of the IUP associated with methotrexate injection have been reported to date [26,29,30]. Two studies reported that the use of hypersmolar glucose was associated with preservation of the IUP.…”
Section: Referencementioning
confidence: 98%
“…Heterotopic pregnancy is diagnosed in the presence of simultaneous gestations at two or more implantation sites. Its occurrence is rare in spontaneous conception with an incidence of 1:30,000, while the incidence is found to be as high as 1% in pregnancy by assisted reproductive technology [1]. We report a case of a spontaneous heterotopic pregnancy that was diagnosed by visualization of heart activity in both intrauterine and extra-uterine gestations.…”
mentioning
confidence: 91%